Pendapatan Usahatani Tanaman Kakao (Teobroma kakao) Di Kelurahan Hinekombe, Distrik Waibu, Kabupaten Jayapura - Metius Wonda; Evawani Tomayahu (Faculty of Agriculture, Pattimura University, 2016)
Kakao is one of important estate commodity for the national economy, since kakao plantation provide a significant number of employment which is support national income and foreign exchange. This study aims to determine farm incomes of kakao farmers in Hinekombein Village, Waibu Subistrict of Jayapura District. Primary data was collected by used of interview and observation guided by a questionnaire. The primary data obtained through interviews with farmers using a questionnaire. Secondary data has been obtained from secondary data sources associated with the research. Sampling was done by simple random sampling for cocoa farmers in Hinekombe Village, number of respondents was 30 farmers cocoa farmers This study showed that annual revenue of cocoa of farmers which has 0.5 of cultivated area was Rp 1,150,556. The revenue of farmer which has 1 ha of cultivated area was Rp. 2.662.500.